2005
DOI: 10.1007/s10508-005-6275-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motivations and Fantasies of Strip Club Customers in Relation to Legal Regulations

Abstract: Strip clubs are a popular form of adult entertainment in the contemporary United States. Strip clubs are also highly embattled entertainment venues, based on assumptions about their associations with prostitution, drug use, and "negative secondary effects" in surrounding areas, such as increased crime rates and decreased property values. Based on participant observation in five strip clubs in one city and on qualitative interviews with 30 regular male customers of those clubs, this essay seeks to challenge ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
0
16
0
4
Order By: Relevance
“…Fine (1991) compared exotic dance with ballet and explained the former's low status in the 1980s and why it is not taught in high school (ballet, certified as part of elite culture, has established critics, expansive venues, charitable events to support it, well-funded companies, international links, textbooks and theories, schools, professional organizations, etc.). Exotic dance is examined as cultural meanings (Calhoun, Cannon, & Fisher, 1996;Frank, 2005;Hanna, 1999), social class (Trautner, 2005), tourist attraction (Donlon, 1998), and amateur contest (Agustin, 2005;Calhoun et al, 1996).…”
Section: Striptease Exotic Dancementioning
confidence: 99%
“…Fine (1991) compared exotic dance with ballet and explained the former's low status in the 1980s and why it is not taught in high school (ballet, certified as part of elite culture, has established critics, expansive venues, charitable events to support it, well-funded companies, international links, textbooks and theories, schools, professional organizations, etc.). Exotic dance is examined as cultural meanings (Calhoun, Cannon, & Fisher, 1996;Frank, 2005;Hanna, 1999), social class (Trautner, 2005), tourist attraction (Donlon, 1998), and amateur contest (Agustin, 2005;Calhoun et al, 1996).…”
Section: Striptease Exotic Dancementioning
confidence: 99%
“…That women unaccompanied by Views, events, and debates men are frequently barred from entry (Roach 2007) is a clear confirmation that they provide access to women in a 'market for men ' (O'Neill 2001, 155). Studies with men who visit clubs have found the appeal rests on interlinked themes: sexualised consumption as a normalised form of leisure, enabling men to 'relax' (Frank 2005); and that men seek 'masculine spaces' where they are not required to interact with women as equals (Frank 2003(Frank , 2005. What is interesting here is how male customers frame sexualised consumption as leisure, and what is worrying is how men seek out contexts where women are not afforded respect as whole persons.…”
Section: Organisation Profile: Women Living Under Muslim Laws (Wluml)mentioning
confidence: 99%
“…Strip clubs are set up as masculine recreational spaces (Frank 2005), and as such, they comprise party culture for workers (strippers, bartenders, and deejays), as well as patrons. Nightlife locales also provide access to drugs and alcohol.…”
Section: The Scene At Mell's Belles: Strip Clubs As Generic Drug Spacesmentioning
confidence: 99%